P218 Nodal Staging In Lung Cancer: A Risk Stratification Model For Lymph Nodes Classified As Negative By Ebus-tbna. (10th November 2014) - Evison, M; Crosbie, P; Morris, J; Martin, J; Shah, R; Barber, P; Booton, R
Abstract : Background: Over the last 10 years, EBUS-TBNA has become established as the first line nodal staging procedure of choice for lung cancer patients. However, the pathway for patients following a negative EBUS-TBNA has not been clearly defined. Aims and objectives: The primary aim of this study was to develop and validate a risk stratification model to categorise lymph nodes deemed negative by EBUS-TBNA into 'low risk' and 'high risk' groups, where 'risk' refers to the risk of false negative sampling. Materials and methods: A retrospective analysis of a prospectively maintained database at a UK tertiary EBUS-TBNA centre. Only patients with primary lung cancer and only negative lymph nodes by EBUS-TBNA were included in the analysis. A risk stratification model was built from a derivation set using independent predictors of malignancy and the validation set used to evaluate the constructed model. The study period was March 2010 to August 2013. Results: 329 lymph nodes were included in the analysis (derivation set n = 196, validation set n = 133). Lymph node SUV, the SUV ratio between the lymph node and primary tumour and heterogeneous echogenicity during sonographic assessment were the only independent predictors of malignancy. Using a simplified scoring system based on the natural logs of the odds ratios from the multivariable analysis on the derivation sample, lymph nodes can be stratified into 'low risk' (score ≤1) and 'high risk' (score ≥2). 141/142 and 94/96 lymph nodes classified as 'low risk' in the derivation and validation set respectively were ultimately proven to be benign and 35/54 and 24/37 lymph nodes classified as 'high risk' were proven malignant. The negative predictive value of the risk stratification model for the derivation set and validation set was 99.3% (95% CI 96.1–99.6) and 97.9% (95% CI 92–99.6%) respectively. Discussion: This risk stratification model may assist lung cancer MDTs in deciding which patients need further staging procedures and which may proceed directly to treatment after a negative EBUS.